Meta-Analysis: The Effect of Malaria Infection on the Incidence of Low Birth Weight - Anggara, Feri Yuda; Rahardjo, Setyo Sri; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: Malaria is a parasitic infectious disease. Malaria contributes to morbidity and mortality in high-risk groups, namely pregnant women and children under five. Malaria infec